2001
DOI: 10.1002/jms.118
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐induced fragmentation of deprotonated methoxylated flavonoids, obtained by electrospray ionization mass spectrometry

Abstract: Electrospray operated in the negative mode was used to analyse methoxylated flavonoids. They were found to produce radical anions by collision-induced fragmentation of the aglycones. Loss of a methyl group from the deprotonated molecule corresponding to [M - H - 15]-* ions, as well as [M - H - 15-28]-* and [M - H - 15-29]- fragment ions, were found to constitute the characteristic fragmentation for the monomethoxylated species, whereas [M - H - 15]-*, [M - H - 30]- and [M - H - 30-28]- were predominant for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
120
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 17 publications
27
120
1
1
Order By: Relevance
“…Thus, the results suggested that the ion at m/z 299 is a methylated derivative of kaempferol. Most commonly, these substituents are linked to C-5 or C-7 of A-ring [29], but its exact position cannot be discriminated by MS analysis. Still, in accordance with Gardana et al [23], the fivederivative flavonoids tend to elute before the aglycones in HPLC reversed-phase conditions, and that was the reason why this position is considered in the present study (Fig.…”
Section: Derivatives Of Common Flavonoids the Phenolic Compounds Relamentioning
confidence: 99%
“…Thus, the results suggested that the ion at m/z 299 is a methylated derivative of kaempferol. Most commonly, these substituents are linked to C-5 or C-7 of A-ring [29], but its exact position cannot be discriminated by MS analysis. Still, in accordance with Gardana et al [23], the fivederivative flavonoids tend to elute before the aglycones in HPLC reversed-phase conditions, and that was the reason why this position is considered in the present study (Fig.…”
Section: Derivatives Of Common Flavonoids the Phenolic Compounds Relamentioning
confidence: 99%
“…Another abundant ion at m/z 169 in the MS/MS spectrum could not be explained by previously known fragmentation pathways. We assumed it should result from the simultaneous cleavage of C 2 OO and C [4][5][6][7][8][9][10][11] bonds. This ion could further fragment into m/z 154 by CID.…”
Section: Identification Of Type I Homoisoflavonoidsmentioning
confidence: 99%
“…Flavonoids, especially flavonols, flavones, and their glycosides, are the most frequently reported [5][6][7][8][9][10][11][12]. Electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) sources are usually used as the interface between HPLC and a mass spectrometer.…”
mentioning
confidence: 99%
“…Therefore, the combination of HPLC and MS facilitates rapid and accurate identification of chemical compounds in medicinal herbs, especially when a pure standard is unavailable. Recently, LC/MS has been extensively used for the analysis of phenolic compounds [17][18][19][20][21][22].°Electrospray°ionization°(ESI)°is°a°preferred°source°due to its high ionization efficiency for phenolic compounds. However, few efforts are devoted to anthraquinones, which are ubiquitously present in plants and show important bioactivities.…”
mentioning
confidence: 99%